"Trapped reentry" as a dormant source of acute focal arrhythmia and fractionated atrial electrograms under sinus rhythm. (25th November 2020) - De Coster, T; Teplenin, A.S; Feola, I; Van Brakel, T.J; De Vries, A.A.F; Zeppenfeld, K; Pijnappels, D.A
Abstract: Background: Diseased atria are characterised by functional and structural heterogeneities (e.g. dense fibrotic regions), which add to abnormal impulse generation and propagation, like ectopy and block. These heterogeneities are thought to play a role in the origin of complex fractionated atrial electrograms (CFAEs) under sinus rhythm (SR) in atrial fibrillation (AF) patients, but also in the onset and perpetuation (e.g. reentry) of this disorder. The underlying mechanisms, however, remain incompletely understood. Purpose: To test the hypothesis that dense local fibrotic regions could create an electrically isolated conduction pathway in which reentry can be established via ectopy and block to become "trapped" (giving rise to CFAEs under SR), only to be "released" under dynamic changes at a connecting isthmus (causing acute focal arrhythmia (FA)). Methods: The geometrical properties of such an electrically isolated pathway, under which reentry could be trapped and released, were explored in vitro using optogenetics by creating conduction blocks of any shape by means of light-gated depolarizing ion channels (CatCh) and patterned illumination. Insight from these studies was used for complementary computational investigation in virtual human atria to assess clinical translation and to provide deeper mechanistic insight. Results: Optical mapping studies, in monolayers of CatCh-activated neonatal rat atrial cardiomyocytes, revealed that reentry could indeed be established and trapped by creating an electrically isolated pathway with a connecting isthmus causing source-sink mismatch. This proves that a tachyarrhythmia can exist locally with SR prevailing in the bulk of the monolayer. Next, it was confirmed under which conditions reentry could escape this pathway by widening of the isthmus (i.e. overcoming the source-sink mismatch), thereby converting this local dormant arrhythmic source into an active driver with global impact (i.e. acute monolayer-wide FA). This novel phenomenon was shown in circuits <0.7cm 2, adding to their probability to exist in human atria. Computational 3D studies revealed that the conditions for "trapped reentry" and its release can indeed be realized in human atria. Unipolar epicardial pseudo-electrograms derived from these simulations showed CFAEs at the site of "trapped reentry" in coexistence with normal electrograms showing SR in the bulk of the atria. Upon release of the reentry through reduction of gap junctional coupling, acute FA occurred, affecting the complete atria as evidenced by wave front and electrogram visualization. Conclusion: This study reveals that "trapped reentry", a previously undesignated phenomenon, can explain the origin of two designated ones: the observation of CFAEs under SR and acute onset of FA. Further exploration of the concept of "trapped reentry" may not only expand our understanding of AF initiation and perpetuation, but also termination, including ablation strategies by site-directed targeting. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): This study was funded by the European Research Council (Starting grant 716509) to D.A. Pijnappels